Dynamic controlled atmosphere: A review of methods for monitoring fruit responses to low oxygen - Thewes, Fábio Rodrigos; Wood, Rachael Maree; Both, Vanderlei; Keshri, Nandita; Geyer, Martin; Pansera-Espíndola, Bruno; Hagemann, Michale Helmut; Brackmann, Auri; Wünsche, Jens Norbert; Neuwald, Daniel Alexandre (Comunicata Scientiae, 2021)
The storage of fruit at minimum oxygen condition is crucial for optimal fruit quality maintenance. However, the optimal oxygen partial pressure of fruit varies according to several factors such as species, cultivar, harvest maturity, temperature, growing season and storage period. Based on these factors, storage technologies were developed that allow for the detection of the lower oxygen limit (LOL) and the storage of fruit under the lowest optimal oxygen partial pressure. One emerging technology is known as dynamic controlled atmosphere (DCA). Commercially, there are four DCA systems used: [1] DCA based on ethanol production and accumulation (DCA-Eth); [2] DCA based on chlorophyll fluorescence (DCA-CF); DCA based on the respiratory quotient (DCA-RQ) and [4] DCA based solely on CO2 production (DCA-CD). This reviews the recent developments of these DCA systems and their effect on fruit quality. Generally, the storage of fruit under DCA has a positive effect on the overall fruit quality, with regards to reduced physiological disorders and higher flesh firmness maintenance, when compared to controlled atmosphere (CA). Evidence also shows that storing fruit under DCA-RQ and DCA-CD allowed higher volatile compound emission and concentration, which can contribute positively to fruit flavor. The DCA systems are “green storage technologies” because the system enables the increase of storage temperature and thereby saving electrical energy. Storage of apples under DCA maintains an overall fruit quality similar to CA combined with the ripening inhibitor 1-Methylcyclopropen (1-MCP), which is an interesting option for organic fruit storage. Dynamic controlled atmosphere is a recently developed storage technique and is in constant improvement. The latest developed DCA techniques (DCA-RQ and DCA-CD), in contrast to DCA-CF, allow the use of extremely low oxygen levels. In the future, new and multi-sensor DCA systems are under development, which might not just control O2 partial pressure but also temperature and other parameters to allow for more energy efficient but high quality fruit storage systems.